Real-Time Environmental Gamma Radiation Dose Rate Measurement around Major Nuclear and Radiological Facilities in Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2018)
Background: In this study, outdoor environmental gamma radiation dose rates were measured at area of Shahbag Thana under Dhaka city and Atomic Energy Research Establishment (AERE) Campus at Savar. Aim of the study: This kind of study is required to detect the presence of natural and artificial radionuclides (if any) releasing from nuclear and radiological facilities in the country or from neighbouring countries. Materials and Methods: The measurement was performed using a real-time portable radiation monitoring device from August-November 2017. The real-time portable radiation monitoring device was placed on tripod at 1 meter above the ground and data acquisition time for each monitoring point (MP) was 1 hour. Total 34 MP were selected around major nuclear and radiological facilities in Bangladesh for collection of dose rate due to gamma-ray. The MPs were marked-out using Global Positioning System (GPS) navigation. The GPS reading of the sampling locations were varied from E90º23’40.08" to E90º24’32.82" and from N23º44’58.62" to N23º43’26.58" for Shahbag Thana and from E90º16’26.58" to E90º16’50.52" and from N23º57’12.96" to N23º57’6.12" for AERE Campus, Savar. Results: The measured dose rates due to natural radionuclides were ranged from 0.105 ± 0.036056 μSv.h-1 to 0.208065 ± 0.106377μSv.h-1 with an average of 0.141568 ± 0.046995 μSv.h-1. The annual effective dose to the population from outdoor environmental gamma radiation was varied from 0.128772 ± 0.044218 mSv to 0.25517 ± 0.130461 mSv and the mean was found to be 0.17362± 0.057635 mSv. This value is lower than some countries like India, China, Sweden, Italy and Czech Republic; and higher than Canada, Mexico, Indonesia, Korea, Turkey, Finland, Spain and some other countries. Conclusion: From this study, it was observed that there is no burden of population exposure due to man-made sources. Therefore, it can be concluded that adequate safety and radiation protection of nuclear & radiological facilities had been ensured which is required for minimizing of unnecessary exposure to populations from man-made sources. The estimated mean annual effective dose found in this study is not expected to contribute significant additional hazard from the radiological health point of view.